Gender Differences in Understanding of Thermal Expansion - Vidak, Andrej (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Investigation of gender differences in science allows us to tailor our instruction to the needs, interests and abilities of all our students. In this study we aimed to investigate gender differences in conceptual understanding of thermal expansion. To that end tenconceptual questions were administered to 195 first year students at the Faculty of Chemical Engineering and Technology, University of Zagreb. Male students significantly outperformed female students. Particularly large differences in favor of males were observed on questions that required reasoning about thermal expansion in one dimension.